Pelatihan Pembuatan Pupuk Organik Cair Dari Limbah Udang Rebon (Kasia) di Kampung Arar Kabupaten Sorong - Nur Abu; La Ibal; Sulfiana Sulfiana; Rahmi Rahmi; Andi Rahayu Anwar; Murni Murni; Nur Miswar; Salmawati Salmawati; Mierta Dwangga; Azalia Fajri Yasin; Nurbia Nurbia; Faridz Macap (LP4MK STKIP PGRI Lubuklinggau, 2024)
This community service activity was conducted in Kampung Arar, Sorong Regency, West Papua, which has abundant potential for rebon shrimp (kasia shrimp). Rebon shrimp are rich in protein, calcium, phosphorus, and iron; however, the washing waste from these shrimp has not yet been utilized by the local community. This activity aimed to provide training to the Kampung Arar community on utilizing rebon shrimp waste to produce liquid organic fertilizer (LOF) using the bioactivator Effective Microorganism (EM4). The methods included socialization, training, and assistance in the LOF fermentation process and its application to plants. The results showed an increase in the community's understanding, particularly among women in the PKK group, regarding the benefits of rebon shrimp waste, with a 70% knowledge improvement after the training. Moreover, the community was able to produce LOF independently and apply it to plants such as water spinach, which exhibited better growth. This activity is expected to contribute to waste management and improve community welfare through sustainable agricultural practices